MODEL PENCEGAHAN PERILAKU KERJA KONTRAPRODUKTIF DI LINGKUNGAN UNIT PELAKSANA TEKNIS (UPT) KANTOR WILAYAH KEMENTERIAN HUKUM DAN HAM SULAWESI TENGGARA (STUDI PADA LPKA KELAS II KENDARI) - Basoddin, Diki; Samdin, Samdin; A. Sabilalo, Mahmudin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
This study aims to formulate a model for preventing counterproductive work behavior within the UPT Regional Office of the Ministry of Law and Human Rights of Southeast Sulawesi (Study on LPKA Class II Kendari). The research design used in this study is qualitative research with a descriptive approach. Qualitative research with a descriptive approach aims to make an accurate and factual picture of the facts found during research. Data analysis uses qualitative descriptive analysis. Overall, this study found six models of prevention of counterproductive work behavior in LPKA Class II Kendari. The six models are: 1) define clear targets; (2) be firm in the implementation of the rules; (3) the leader becomes a role model; (4) reward and punishment; (5) improvement of control and supervisory functions; and (6) the construction of Integrity Zones.